Fixed Point Theorems for α−ψ−Quasi Contractive Mappings in Metric-Like Spaces - Vildan Ozturk (International Journal of Analysis and Applications, 2015)
In this paper, we give fixed point theorems for α − ψ−quasi contractions and α − ψ − p−quasi contractions in complete metric-like spaces.